2019
DOI: 10.1111/bjet.12831
|View full text |Cite
|
Sign up to set email alerts
|

TAM and stages of adoption of blended learning in higher education by application of data mining techniques

Abstract: The purpose of the study is to analyse and identify the stages of adoption of the blended learning (BL or b‐learning) methodology in higher education contexts, and to assess the relationship of these stages with a set of variables related to personal and professional characteristics, attributes perceived on BL and contextual variables. About 980 active academic staff from 43 Spanish public universities participated. The technology acceptance model (TAM) was used as a theoretical framework for the operational d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 49 publications
1
19
0
4
Order By: Relevance
“…For the first three hypotheses, the focus was on the factors of PEU and PU. The hypotheses seem to be consistent with previous studies, that is, the fact that usefulness of Google Meet is governed by its of ease of use seems to be agreed upon by much prior research where colleges and universities were encouraged to focus on the factors of usefulness and ease of use (Martín-García et al, 2019;Rafique et al, 2020). For the fourth hypothesis, where SN factor was investigated, the results have shown that peer's opinions have an effective role in creating an influential educational environment.…”
Section: Discussionsupporting
confidence: 83%
“…For the first three hypotheses, the focus was on the factors of PEU and PU. The hypotheses seem to be consistent with previous studies, that is, the fact that usefulness of Google Meet is governed by its of ease of use seems to be agreed upon by much prior research where colleges and universities were encouraged to focus on the factors of usefulness and ease of use (Martín-García et al, 2019;Rafique et al, 2020). For the fourth hypothesis, where SN factor was investigated, the results have shown that peer's opinions have an effective role in creating an influential educational environment.…”
Section: Discussionsupporting
confidence: 83%
“…Use was made of the Cuestionario sobre Modalidad Formativa Combinada en las Universidades (Questionnaire on the Blended Learning Method at Universities), created and validated beforehand by the research team (Martín and Sánchez 2014;Martín, Martínez, and Reyes 2019). As a self-report measure, the instrument is divided into three blocks of content.…”
Section: Instrumentmentioning
confidence: 99%
“…Esta formación previa tiene un efecto positivo sobre las creencias y la actitud favorable de los profesores y, en definitiva, sobre la implementación de la enseñanza combinada. Resultado constatado también en la literatura especializada (Duarte et al 2018;Fernández-Rodrigo et al, 2019;López et al, 2019;Martín-García et al, 2019b).…”
Section: Conclusionesunclassified
“…Nuestros resultados apoyan la relación entre una mayor experiencia de uso de entornos de formación y competencia digital con fases más altas de implementación de la metodología B-learning conforme a los estadios tipificados en nuestro trabajo. Resultado que coincide con otros presentes en la literatura especializada en el que se observa como el éxito del e-Learning o del B-learning tienen una clara relación con la familiaridad y manejo de plataformas y recursos tecnológicos (Jornet et al, 2012;Picciano & Seaman, 2007;Martín-García et al, 2019a;Martín-García et al, 2019b).…”
Section: Conclusionesunclassified